The Role of Audience Monitoring Surveys (AMS) In Strengthening Radio Talk Shows (RTS) By UNICEF Ethiopia on Female Genital Mutilation (FGM) and Child Marriage Programs - Ahmed, Haithar; Akullu, Harriet; Maksud, Nankali; Sani, Massimiliano; Brooks, Andrew; Aika, Mona; Sharma, Rachana; Challa, Andinet; Terefa, Fikereselam Getinet; Shikur, Zemzem; Westering, Jolanda Van; Mabirizi, Joseph (Advances in Social Sciences Research Journal, 2023)
Female Genital Mutilation (FGM) and child marriage (CM) are some of the worst harmful practices rampant in Ethiopia. Population Media Center-Ethiopia (PMC-E), in partnership with UNICEF and UNFPA, have been broadcasting radio talk shows (RTS) in select regions of the country to address these issues. The main objective of this study was to establish the popularity and relevance of these shows in addressing the issue of FGM and CM. Specific objectives were establishing respondent awareness of the shows, analyzing the knowledge gained from the issues raised in the shows, establishing the convenience of RTS broadcasting times to listeners, and offering suggestions for improvement. The study used a cross-sectional population-based household survey design in which men and women aged 15 – 49 years were interviewed in two phases. A total of 860 respondents in Phase I and 741 in Phase II were interviewed using questionnaires. Data was analyzed descriptively. Findings show that the reach of RTS was not good, attributable to lack of access to radio, mobile phone, or/and lack of electricity or time to listen to the shows. The content, time and presenter skills and creativity were convenient to listeners and the popular topics discussed were FGM, CM, and gender equality. There was a significant difference between people who listened to the shows and those who didn’t in regard to understanding FGM and CM issues. The study recommends government of Ethiopia subsidize the cost of radios purchased by people in target areas as well as promote the use of alternative media to present topics discussed in the RTS.